TEKNIK PENGAMBILAN EKSPRESI LOGIKA MENJADI BENTUK NORMAL DISJUNGTIF DAN NORMAL KONJUNGTIF - Arfida, Septilia (IIB Darmajaya, 2012)
Logic holds an important role in Computer AcademicÂ is used as a basic for programming language, Data Base, Artificial Intelligent, Software Engineering, and etc. Logic is one of knowledge which canât stand alone. It can be used to evaluate and organize the structure of arguments and statements which are collected from the study of the argument and formal system effect to daily human language. Normal form is a standard form for the expression of logic The standard form is meant is that all forms of logic expressions can be simplified by using the basic couplingsÃ, Ã, and Ã. Normal form is two which is disjunctive and konjungtive. Disjunctive Â Normal form using couplings disjunction of conjunction while wearing couplings konjungtive Normal Form. ofÂ the disjunction of conjunctions. Keywords: Normal Form,Â Conjunctive Normal Form, Disjunctive Normal Form